Efficient Controller Positioning in SDN - Kanwar, Pratibha (My University, 2018)
There has been a major advancement in the technology as it is changing at a faster rate every day, developing things better and increasing the efficiency by generating new generation technology. Software Defined Networks (SDN) have developed a lot since it came into the existence and is still evolving, giving new and better application prospects. Controller Placement Problem is a very important prospect of SDN, networking and this research aims at contributing something efficient and better than the already existing work. Controller Placement is one of the major concerns of SDN, networking, designing and placement are essential as to get the best fit solutions for the efficient functioning of a network. Traffic Engineering (TE) is an important network application in Software Defined Networks (SDN) which contributes by providing the measurements and the management of network traffic, designing better routing mechanisms for analyzing and predicting the network flow. This research focuses over the controller placement in SDN for efficient networking throughputs and to perform Traffic Engineering (TE) for analyzing and predicting the flow in the network to sort the traffic management and load balancing in SDN along with some of the important factors which can be improvised and used for an overall smart performance of the network.
M. Tech Thesis
Keywords: Software Defined Network; Latency; Load Balancing; Transmission Rate; Time Efficiency